Silicon nanocrystals as light converter for solar cells - Švrček, V.; Slaoui, A.; Muller, J.-C. (Thin solid films, 2004)
In this work, we investigate the potential use of silicon nanocrystals (Si-nc) into photovoltaics technology as one possible way to increase the silicon solar efficiency at low cost. The Si-nc were prepared ex situ (pulverizing of electrochemical etched porous silicon), embedded into spin-on-glass antireflecting SiO 2 based solution and then spun onto standard silicon solar cells. The Si-nc/SiO 2 layer serves as a luminescence down-converter. Indeed, the high energetic photons are absorbed within the converter ‘Si-nc’ and transformed via its photoluminescence (PL) to red ones (∼700 nm) which are then converted much more efficiently in silicon solar cell. We first quantify the size of the Si-nc. Then we present investigations of Si-nc based converter with different PL intensities and its influence on solar cell performances (internal quantum efficiency (IQE), current–voltage characteristic). We observe increase in IQE in the region where the PL of Si-nc appears. We also report the correlation between the converter PL intensity and IQE. To get insight into the potential of such converter, we introduced a simplified one-dimensional model. The results of the modelling are shown and compared with experimental data.